CREATIVITY: SCULPTING THROUGH DIGITAL PLATFORMS AND NATIONAL EDUCATIONAL POLICY - K, Praneetha; R, Vijayalakshmi (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Education as a platform makes learners develop their knowledge and makes them reach creative levels. It also makes the learner face the world with confidence. Education as a system has undergone many changes with the passage of time. Covid -19 had brought a major shift in the education system and the mode of education. It can be observed that learners from all over the world had shifted to Computer Assisted Language Learning (CALL) and Mobile Assisted Language Learning (MALL). The mode of regular chalk and talk method is completely shifted to Distance learning. The major shift to "MALL" for educational purposes was indeed tough for both the instructors and the learners. So, the major shift can be observed in the field of Ed-tech applications, language learning, and educational policy too., where learners preferred to enroll in online platforms for their growth simultaneously with enrolment in universities. Taking this into consideration the researchers try to examine the growth in the usage of Ed-tech applications with linkage to educational policy 2020. This paper also examines the advantages of online Ed-tech and digital applications.